Pemanfaatan Media Sosial Dalam Meningkatkan Praktik Kalam Bahasa Arab Mahasiswa STEI Permata Bojonegoro - Siti Imaniatul Muflihatin; Faridatun Najiyah (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2023)
In an interaction, language has an important role as a communication medium to increase interaction between individuals for a creative, innovative, adaptive life in understanding the values ​​and norms that exist in society. Language learning is the starting point in mastering a particular language. Speaking skills (maharat al-kalam) are one of the skills that must be achieved in learning Arabic. Speaking is the ability to express articulatory sounds or words to express thoughts in the form of ideas, opinions, desires or feelings to a conversation partner. Use of media Social media in the global era has become a basic need for individuals or groups who do it online to interact with each other without being limited by space and time as a form of technological progress during the Covid-19 pandemic. Social media in the world of education is functionally conditioned as a form of collaboration, friendliness and creativity of its users. Social media supports learning materials to strengthen learning materials at the educational level, including at tertiary institutions.